Dural Arteriovenous Fistula with Bilateral Agenesia of Intracranial Venous Sinuses: A Case Report - Fernando Orozco; José Sáenz; Valeria Almeida; Jose Ospino; Ginna De La Rosa; Rafael Almeida (Radiology Case Reports)
A 27-year-old male patient presented with a history of long-standing headaches, progressive head circumference growth, and a ventriculoperitoneal shunt valve placement in 2018. He was referred for consultation and underwent endovascular neurosurgery in 2019 due to MRI findings suggestive of a cerebral arteriovenous malformation. A neurosurgical board was convened to discuss findings from cerebral panangiography and endovascular treatment options. Cerebral panangiography revealed a Cognard type IV dural arteriovenous fistula, leading to the recommendation of endovascular treatment with Phil embolizing liquid material and a triaxial balloon to reduce venous hypertension. Catheterization was performed through a posterior branch of the right meningeal artery directly afferent to the fistula. A second intervention was performed 6 months later, again utilizing endovascular therapy with Phil embolizing liquid material and balloon via the right femoral artery. The intervention revealed a remnant of the dural arteriovenous fistula with a venous aneurysm in the right sinus. Over a period of several years, 3 additional interventions were performed at intervals of approximately 7 months, achieving partial occlusion. During the fifth intervention, the patient exhibited neurological deterioration, prompting further imaging studies to assess thrombosis of the longitudinal sinus. Endovascular treatment with embolizing liquid material and corticosteroid therapy was administered.